Developing problem-based learning electronic student worksheet for number pattern topic - Prasetyo, Puguh Wahyu; Atsila, Khasna Salma (Universitas Ahmad Dahlan, 2022)
The background of this research is the lack of technology-based learning materials, teachers, and students' need for the variety of new learning materials in SMP Negeri 1 Bantarkawung. This study aimed (1) to produce problem-based learning electronic student worksheets for number patterns and (2) to know the usefulness of problem-based learning electronic student worksheet for number patterns in terms of validity and practicality. It was the R&D (Research and Development) using ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. This research was conducted in class VIII A SMP Negeri 1 Bantarkawung involving six students in a small class trial and twenty-eight students in a big class trial. The research instruments were interview guidelines and questionnaires to material experts, media experts, and students' responses. The results showed that students' electronic worksheets were valid and practical. The evaluation by students' electronic worksheet material expert got 70,50, categorized as very valid. The review from media experts showed that Students' Electronic Worksheet got 68,50, which was classified as very valid. Meanwhile, the small class trial got 62,84, categorized as practical. Moreover, the big class trial got 65,39, and was classified as practical.